G529(P) Enteral feed exposures in preterm infants born less than 32 weeks in England. (7th April 2014) - Battersby, C; Santhakumaran, S; Fitz-Simon, N; Modi, N
Abstract : Aims: Feeding strategies are widely believed to influence the susceptibility of preterm infants to Necrotising Enterocolitis (NEC) but due to limited available evidence, there remains to be uncertainties regarding the optimal feeding strategy. We aimed to describe and explore factors which influenced the time to first feed and formula in preterm infants cared for in 146 neonatal units in the UK Neonatal Collaborative (UKNC)-NEC study. Methods: 26 variables from infants born between 23 and 31+6 weeks and admitted in 2012 was extracted from the National Neonatal Research Database. For infants who were fed during neonatal care, the median and interquartile range for days to first feed is reported by gestational age. A flexible competing risks model was used to model the cumulative incidence of commencement of enteral feeds and formula, taking into account the time-dependent effect of gestation. This study is funded by Medicines for Neonates Programme and received research ethics approval (11/LO/1430). Results: The analysis included 6641 infants. Daily type of feed was well completed (98%). For 6347 infants who were fed during neonatal care, the median and interquartile (IQ) range of days to first feed was 4 (3–6) for infants born 24 weeks and 2 (2–3) for babies born 30 weeks. There was a statistically significant effect of gestation on time to first feed and time to formula (p < 0.0001 from likelihood ratio test comparing models with and without gestational age terms), with the more mature infants receiving first feed and formula earlier, but the effect of gestational age reduces over time. Conclusion: The time to first feed and introduction of formula is inversely associated with gestational age. Infants of younger gestational ages are less likely to receive formula and commencement of feeds is delayed compared to more mature babies. It is unknown whether this cautious approach to feeding in infants of younger gestational ages influences the development of NEC and this will be explored further in the UK Neonatal Collaborative-NEC Study.